ILLOCUTIONARY ACTS IN STAND-UP COMEDY - Giel Utami Putri; Sri Minda Murni (State University of Medan, 2012)
ABSTRACT This research was conducted to discover the types of illocutionary acts, the most dominant type of illocutionary acts, the implication of the dominant type of illocutionary acts, and which utterances show the function of stand-up comedy in stand-up comedy performances in Indonesia. It was based on descriptive design by applying both quantitative and qualitative method. This study took ten performances of stand-up comedy which is taken randomly from the internet and there were 1378 illocutionary acts in ten stand-up comedy selected. The findings show that all types of illocutionary acts were used in stand-up comedy and the percentages were: 55.9% of representatives, 22.9% of directives, 16.2% of expressives, 3% of declaratives and 2% of commissives. There was another function of stand-up comedy in addition to entertaining, informing, and criticizing, which is insinuating. The most dominant illocutionary acts type found was representatives. It means, in delivering their material, the comics dominantly convey their belief that some proposition is true and they also indirectly provoke the audience to believe their words. Keywords: Illocutionary Acts, Stand-Up Comedy.